Aged Garlic Extract Improves Adiponectin Levels in Subjects with Metabolic Syndrome: A Double-Blind, Placebo-Controlled, Randomized, Crossover Study. (28th February 2013) - Gómez-Arbeláez, Diego; Lahera, Vicente; Oubiña, Pilar; Valero-Muñoz, Maria; de las Heras, Natalia; Rodríguez, Yudy; García, Ronald Gerardo; Camacho, Paul Anthony; López-Jaramillo, Patricio
Abstract : Background . Garlic ( Allium sativum ) has been shown to have important benefits in individuals at high cardiovascular risk. The aim of the present study was to evaluate the effects of the administration of aged garlic extract (AGE) on the risk factors that constitute the cluster of metabolic syndrome (MS). Methods and Design . Double-blind, crossover, randomized, placebo-controlled clinical trial to assess the effect of 1.2 g/day of AGE (Kyolic), for 24 weeks of treatment (12 weeks of AGE and 12 weeks of placebo), on subjects with MS. Results . The administration of AGE increased the plasma levels of adiponectin (P = 0.027 ). No serious side effects associated with the intervention were reported. Conclusion . The present results have shown for the first time that the administration of AGE for 12 weeks increased plasma adiponectin levels in patients with MS. This suggests that AGE might be a useful, novel, nonpharmacological therapeutic intervention to increase adiponectin and to prevent cardiovascular (CV) complications in individuals with MS.